Propuesta De Una Zonificación Ambiental Para La Recuperación De Conectividad Del Paisaje A Partir Del Análisis Morfológico Del Terreno Y Coberturas De La Tierra En La Finca Morichales Del Municipio De Puerto Lopez, Departamento Del Meta, Colombia (2025)
In recent years, Geographic Information Systems (GIS) tools have increasingly become a more affordable option for gathering the necessary information for strategic territorial planning. These tools allow for the spatial evaluation of countless variables and parameters, providing both public and private sector users with low-cost resources for the development of various activities.